Anadromy and marine habitat use of Lake trout (Salvelinus namaycush) from the central Canadian Arctic - Harris, Les N.; Swanson, Heidi K.; Gilbert, Matthew J.H.; Malley, Brendan K.; Fisk, Aaron T.; Moore, Jean Sébastien (Journal of Fish Biology, 2020)
Anadromy was documented in 16 lake trout, Salvelinus namaycush, from Canada's central Arctic using capture data and otolith microchemistry. For the first time, estuarine/marine habitat use was described for five individuals using acoustic telemetry. Age-at-first-migration to sea was variable (10–39 years) among individuals and most S. namaycush undertook multiple anadromous migrations within their lifetime. Telemetry data suggested that S. namaycush do not travel far into marine habitats and prefer surface waters (<2 m). These results further our collective understanding of the marine ecology of Arctic S. namaycush.